An operative case of malignant mediastinal germ cell tumor (seminoma) markedly responsive to induction chemotherapy - Ishikawa, Kiyoshi; Genka, Keiichiro; Kawabata, Tsutomu; Kuniyoshi, Masayuki; Ohta, Morio (Nihon Kokyuki Geka Gakkai zasshi (Kyoto, 1992), 2000)
An 18-year-old boy was admitted to our hospital with anterior chest pain. Chest X-ray and CT scan showed a huge mass on the anterior mediastinum. Laboratory examination revealed high levels of serum human chorionic gonadotropin (HCG). The diagnosis of primary anterior mediastinal germ cell tumor was made by preoperative percutaneous needle biopsy. Preoperative two courses of cisplatin-based combination chemotherapy were administered. The serum HCG level decreased rapidly to a normal level and tumor size was extremely reduced. Combined resection of the tumor and adjacent pulmonary and pericardial tissue was carried out through a median sternotomy. One course of the combination chemotherapy was added postoperatively. Seven years after the surgery, he has no signs of recurrence. In conclusion, preoperative cisplatin-based combination chemotherapy is effective, and aggressive surgical procedure is indicated for the treatment of mediastinal germ cell tumor.